Hubungan Tingkat Kepatuhan Physical Distancing dengan Kejadian COVID-19 di Kota Medan - Sinaga, Jianni Herawaty; Simanjuntak, Novita Hasiani; Sitepu, Jenny Novina (Nommensen Journal of Medicine, 2023)
Background: During the COVID-19 pandemic in Indonesia, 1086 pregnant women and 302 babies died from COVID-19 infection in 2021. The high mortality rate affecting ANC visits was seen from the decrease in ANC coverage, influenced by knowledge, attitudes, and anxiety. Objective: To see if there is a relationship between social distancing and the incidence of COVID-19. Methods: This study was an analytical study with a cross-sectional design. The sample selection used the snowball sampling method, and 222 samples were obtained which were assessed using an online questionnaire via google form. Results: The 83,3% of respondents did not obey physical distancing and 11,7% of respondents were classified as COVID-19 incidents. Data analysis with Fisher's exact test obtained p value = 0,089 (p> 0,05). Conclusion: There is no relationship between the level of compliance with physical distancing and the incidence of COVID-19 in Medan. Keywords: COVID-19, level of compliance, incidence of COVID-19